(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
his paper presents an approach to the construction history of “saca de agua” or the aqueduct of Cedazo, initiated by the mayor Matías de la Mota in 1731 at a great cost. he discussion starts with a description of how it was founded as a water supply system in the town of Aguascalientes. he works were suspended at the middle of the 18th century and started again as late as in 1827, during the period of the irst federal republic. In 1891, the aqueduct underwent general refurbishment. he present paper describes the diferent stages of its construction, pointing out the diiculties which emerged in each of them. It is essential to highlight the importance of this work and the way it resulted in a qualitative improvement of the city’s water supply. he aqueduct’s qanat character is also discussed in the article and therefore also its connection to the ancient building tradition coming from the Near East, which was introduced in America by the Spanish conquerors and colonizers from the 16th century onwards. he core of this paper is based on original documentation from archives and is a contribution to the studies on environmental history, in particular on water supply and use.